Effects of drying methods on the structure and emulsifying capacity of egg yolk lecithin - Bai, Xiting; Gao, Jiaqi; Yang, Yu; Zhu, Wenxue; Fan, Jinling (International Journal of Agricultural and Biological Engineering, 2020)
The purpose of this study was to investigate the effects of different drying methods, including ultrasonic vacuum drying, vacuum drying, vacuum freeze-drying, hot-air drying and spray drying, on the structure and emulsifying capacity of egg yolk lecithin based on Raman spectra. The results showed that ultrasonic vacuum drying and spray drying can induce the vibration of C–N bonds in the polar O–C–C–N+ head skeleton of egg yolk lecithin. The shift of the peak attributed to the C–N bond from 717 cm−1 to 774 and 772 cm−1 indicated that the vibration of some C–N bonds in the O–C–C–N+ skeleton had transformed from gauche to trans. Ultrasonic vacuum drying exerted the most intense effect on the C–C skeleton of egg yolk lecithin, with the greatest vibration peaks at 1062 cm−1, 1128 cm−1, and 1097 cm−1 in the Raman spectra of egg yolks. Specifically, it relieved gauche vibration and strengthened trans vibration in the C–C skeleton. Hence, the Igauche/Itrans ratio of the egg yolk lecithin processed through ultrasonic vacuum drying decreased. Ultrasonic vacuum drying and spray drying decreased the I2850/I2878 ratio of the vibration peak of C–H bonds in the lipid chains of egg yolk lecithin. The weakening of the symmetric stretching vibration of the C–H bond and the strengthening of antisymmetric stretching vibration indicated that orderliness among the molecular chains of lipid bilayer membranes had increased, whereas liquidity had decreased. The emulsifying capacities were highly significantly different among various egg yolk lecithin samples, in which the highest emulsifying capacity (49.58 m2/g) was shown for the egg yolk lecithin prepared through vacuum freeze-drying, and ultrasonic vacuum drying produced the lowest emulsifying capacity (14.77 m2/g). This study demonstrated that ultrasonic vacuum drying and spray drying drastically affected the structure of egg yolk lecithin. The appropriate drying method can be selected based on sample volume and production situation. Keywords: drying, structure, emulsification capacity, egg yolk lecithin, Raman spectrum DOI: 10.25165/j.ijabe.20201304.5648 Citation: Bai X T, Gao J Q, Yang Y, Zhu W X, Fan J L. Effects of drying methods on the structure and emulsifying capacity of egg yolk lecithin. Int J Agric & Biol Eng, 2020; 13(4): 238–244.